(untitled) (Hilo Analítico, 2021)
Perhaps talking about life and death is one of the most confusing topics, the repressed ideations as a result of domestic violence are currently a tragicomedy, but by joining the points of existence now everything can be seen more clearly and before this, the end Life has two enormous perspectives, one such as Suicide and a particular view such as Euthanasia, initially according to the World Health Organization (WHO), 900,000 suicides are committed each year in the world, a rate of 16 per 100,000 inhabitants. , somewhat disturbing indicators, we will not know if death is a way out from pain or those situations where unresolved conflicts are reflected in melancholy